Dancing behavior of Cosmopterix victor Springer, a species new to the fauna of China (Lepidoptera: Cosmopterigidae). - Davis, Steven R.; Sinev, Sergej Yurjevitsch (Contributions to Entomology = Beiträge zur Entomologie, 2008)
A bamboo-feeding species Cosmopterix victor Stringer, 1930 is mentioned from mainland Asia for the first time, with a description and illustration of its very striking dancing behavior. This behavior is regarded as a special adaptation providing the aggregation of adults on the host plants for mating and subsequent oviposition. Keywords Microlepidoptera, Zhejiang Province, Cosmopterigidae, Cosmopterix victor, dancing behavior.